PENINGKATAN MOTIVASI BERINOVASI UNTUK KELANGSUNGAN USAHA PEDAGANG DI KELURAHAN SUKAMAJU KECAMATAN CIBEUNYING KIDUL - Anggapradja, Indra Taruna; Marinda, Vina Silviani (ADIMAS Jurnal Pengabdian Kepada Masyarakat, 2024)
As a densely populated area, Cibeunying Kidul District does not have rice fields. In BPS data, it is stated that Cibeunying Kidul has non-rice fields covering an area of 515.34 hectares. As a residential area that relies on the trade sector, in Cibeunying Kidul there are 10 government-managed banks. In facing rapid changes in times and technology, traders are required to always innovate. The tastes of potential consumers are always dynamic as time goes by, especially now that we have entered the digital era. This community service activity aims to help, accompany and increase the motivation of traders in Cibeunying Kidul District. This activity also aims to introduce promotional media and easy payment methods to make trading transactions easier. This Community Service Activity will be held from February to June 2023. The methods used in this activity are field surveys and interviews with traders in Sukamaju Village, Cibeunying District. The purpose of the field survey carried out is the method used to gain a better understanding of the problems faced by the community that is the target of community service, as well as to identify potential solutions that can be implemented. The result was that participants were advised to try creating social media accounts such as Instagram and Tiktok to introduce their products and for technological improvement innovations, speakers from Widyatama University explained the benefits of payments or transactions using the Indonesian Standard QR Code (QRIS).